2017
DOI: 10.1002/kpm.1539
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐Sharing Networks: Language Diversity, Its Causes, and Consequences

Abstract: Although it is recognized that diversity influences knowledge sharing between employees, there is very little empirical research on the relationship between language diversity and knowledge sharing in the organizations. In this context, this study adopts network perspective and explores linguistic composition of personal knowledge‐sharing networks, its causes and consequences. A survey was conducted involving 403 participants in different subsidiaries of a multinational organization. Hierarchical regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 64 publications
(115 reference statements)
1
26
0
Order By: Relevance
“…Knowledge sharing is the process of knowledge creation, dissemination and inflow in an organization as well as in a network of organizations (Ahmad, 2017; Haas & Hansen, 2007). Inter‐organizational knowledge sharing is the dissemination and inflow of knowledge beyond the organizational boundaries through networking of different organizations (Gulati, Nohria, & Zaheer, 2000; Wang, Sharma, & Cao, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge sharing is the process of knowledge creation, dissemination and inflow in an organization as well as in a network of organizations (Ahmad, 2017; Haas & Hansen, 2007). Inter‐organizational knowledge sharing is the dissemination and inflow of knowledge beyond the organizational boundaries through networking of different organizations (Gulati, Nohria, & Zaheer, 2000; Wang, Sharma, & Cao, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data gathered during the interviews were subjected to qualitative content analysis, due to the linkage between knowledge and language (Ahmad, ; Kohlbacher, ; Krone et al, ). This research method represents a data reduction technique, characterized by “a systematic and replicable method for compressing many words of text into fewer content categories based on explicit rules of coding” (Stemler, ).…”
Section: Methodsmentioning
confidence: 99%
“…In detail, this study attempts to understand if it is possible to identify the antecedents of interorganizational knowledge creation within a network‐based strategic project, and how this may be achieved. The relation between knowledge and language, highlighted by the deutero learning processes framework, leads to the adoption of qualitative content analysis as research methodology (Ahmad, ; Krone, Syväjärvi, & Stenvall, ). The latter has been applied to the case study in analysing, elaborating, and interpreting the data gathered by means of direct interviews with farmers involved in the project.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As information sharing plays an integral role in organizational success, the means to improve it has emerged as a focal area of investigation. Previous research has identified a number of factors-including organizational culture, diversity, personality, sense of coherence, and compensation-that influence information sharing between employees (Ahmad, 2017a;Shin, Ishman, and Sanders, 2007;Yang and Maxwell, 2011).…”
Section: Introductionmentioning
confidence: 99%